Comparative Genomic Analysis of the Regulation of Aromatic Metabolism in Betaproteobacteria - Suvorova, Inna A.; Gelfand, Mikhail S. (Frontiers in Microbiology, 2019)
Aromatic compounds are a common carbon and energy source for many microorganisms, some of which can even degrade toxic chloroaromatic xenobiotics. This comparative study of aromatic metabolism in 32 Betaproteobacteria species describes the links between several transcription factors (TFs) that control benzoate (BenR, BenM, BoxR, BzdR), catechol (CatR, CatM, BenM), chlorocatechol (ClcR), methylcatechol (MmlR), 2,4-dichlorophenoxyacetate (TfdR, TfdS), phenol (AphS, AphR, AphT), biphenyl (BphS), and toluene (TbuT) metabolism. We characterize the complexity and variability in the organization of aromatic metabolism operons and the structure of regulatory networks that may differ even between closely related species. Generally, the upper parts of pathways, rare pathway variants, and degradative pathways of exotic and complex, in particular, xenobiotic compounds are often controlled by a single TF, while the regulation of more common and/or central parts of the aromatic metabolism may vary widely and often involves several TFs with shared and/or double or cascade regulation. The closest and most variable connection exists between AphS, AphR, AphT, and BenR. We have identified a new LysR-family TF that regulates the metabolism of catechol (or some catechol derivative) and either substitutes CatR(M)/BenM, or shares functions with it. We have also predicted several new members of aromatic metabolism regulons, in particular, some COGs regulated by several different TFs.